OPTIMASI RUTE PENGANGKUTAN SAMPAH DI KOTA LAMONGAN DENGAN MENGGUNAKAN METODE SAVING MATRIX - Wardatul Jannah (Indonesian Journal of Spatial Planning, 2020)
The system and transport of waste is one of the most expensive elements of waste management  system  in  city.  According  to  Apaydin  (2007),  the  system  and transport  of  waste  requires  about  85%  of  the  total  waste  management  system. Meanwhile, according to Damanhuri (2010) transportation costs of waste is 50% - 60% of the total cost of waste management. Limitations of funds allocated by the Lamongan  District  Government  for  waste  management  is  another  problem  that adds to the complexity of waste problems, especially by means of waste transport. The  impact  is  waste  accumulation  in  some  areas.  This  research  is  conducted  to give recommendation of waste transportation route optimally using saving matrix method in the Lamongan city. Saving Matrix method is one of the methods used to determine the optimal route of waste transportation by minimizing the distance and travel time based on the transport load so that the shortest route and minimum transportation  cost  are  obtained.  This  research  resulted  14  routes  of  waste transportation  at  Lamongan  City  with  total  distance  120.24  km  with  total  time 180.33 minutes. Total cost monthly is Rp. 9.288.540, -. So from the use of saving matrix method can save costs Rp. 656.625- per month or Rp. 7.879.500 - per year.